The Influence of Social Comparison and Peer Group Size on Risky Decision-Making - Wang, Dawei; Zhu, Liping; Maguire, Phil; Liu, Yixin; Pang, Kaiyuan; Li, Zhenying; Hu, Yixin (Frontiers in Psychology, 2016)
This study explores the influence of different social reference points and different comparison group sizes on risky decision-making. Participants were presented with a scenario describing an exam, and presented with the opportunity of making a risky decision in the context of different information provided about the performance of their peers. We found that behavior was influenced, not only by comparison with peers, but also by the size of the comparison group. Specifically, the larger the reference group, the more polarized the behavior it prompted. In situations describing social loss, participants were led to make riskier decisions after comparing themselves against larger groups, while in situations describing social gain, they become more risk averse. These results indicate that decision making is influenced both by social comparison and the number of people making up the social reference group.